Pyrogallic acid: A novel depressant for bismuthinite in Mo–Bi sulfide ore flotation. (15th January 2019) - Lin, Shangyong; Liu, Runqing; Sun, Wei; Hu, Yuehua; Gao, Zhiyong; Han, Haisheng
Highlights: Pyrogallic acid exhibit selective depression effect on bismuthinite flotation. Pyrogallic acid expanded the difference in flotation rate of both minerals. Pyrogallic acid has a destabilizing effect on the froth phase. Abstract: Molybdenum ore flotation techniques are constantly challenged by the emergence of complex sulfide minerals, such as bismuthinite, in the mineral processing industry. Conventional flotation depressants, such as sodium sulfide, used in Mo–Bi-containing ore flotation require high dosages, which leads to high cost and low selectivity. Therefore, in this study, pyrogallic acid (PA), a widely distributed organic source, is tested as an alternative depressant to selectively depress bismuthinite in Mo–Bi sulfide ores from Shizhuyuan. Results show that PA has a minimal effect on molybdenite recovery; by contrast, PA has a high depressing effect on bismuthinite amelioration. At 500 g/t PA, molybdenum recovery slightly decreases by 2 percentage points, and bismuth content in molybdenum concentrate sharply declines by 34 percentage points, with respect to samples floated without PA. Batch flotation tests demonstrate that PA addition affects froth stability, as indicated by the variations of solid and water recoveries. The superior selectivity of molybdenite over bismuthinite is promoted by increasing the PA dosage. On the basis of these findings, PA is a feasible option and thus can be used as a depressant for bismuthinite in the flotation of sulfide minerals.